Surface illuminator using point light source - IIMURA KEIJI (2005)
The disclosed apparatus is a surface illuminator i.e. surface light source typically used in lighting for liquid crystal displays (LCDs). The surface illuminator using point light source may comprise a first light guide member for a surface lighting having a first light exiting surface and a first light entering surface; a second light guide member for a light distribution having a second light exiting surface and a second light entering surface; at least one point light source (LED) optically communicated with the second light entering surface; a channel light guide member having a fiber optic channel array having a plurality of light guiding portions optically isolated one another; and wherein the channel light guide member is disposed between the first light guide member and the second light guide member. The second light guide member may be an elongated light guide member having a linear or nonlinear elongated member.